Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1073/pnas.1720510115
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a hexagonal ultradense hydrous phase in (Fe,Al)OOH

Abstract: A deep lower-mantle (DLM) water reservoir depends on availability of hydrous minerals which can store and transport water into the DLM without dehydration. Recent discoveries found hydrous phases AlOOH ( = 2) with a CaCl-type structure and FeOOH ( = 4) with a cubic pyrite-type structure stable under the high-pressure-temperature () conditions of the DLM. Our experiments at 107-136 GPa and 2,400 K have further demonstrated that (Fe,Al)OOH is stabilized in a hexagonal lattice. By combining powder X-ray-diffracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…We may expect the new iron superoxide in pyrite structure to accommodate and form solid solutions with other divalent and trivalent cations such as Mg 2+ and Al 3+ (ref. 48 ) and with anions, such as sulfur and halogens. We may further expect that the peroxide structure is only one example of the possible compositions in the deep Earth, and that additional structure types with different valence and spin, such as the recently discovered hexagonal phase 48 , will emerge.…”
Section: Discussionmentioning
confidence: 99%
“…We may expect the new iron superoxide in pyrite structure to accommodate and form solid solutions with other divalent and trivalent cations such as Mg 2+ and Al 3+ (ref. 48 ) and with anions, such as sulfur and halogens. We may further expect that the peroxide structure is only one example of the possible compositions in the deep Earth, and that additional structure types with different valence and spin, such as the recently discovered hexagonal phase 48 , will emerge.…”
Section: Discussionmentioning
confidence: 99%
“…The major components of the lower mantle are made of nominally anhydrous minerals, which contain no more than 1 weight percent of water [1,2]. However, recent discoveries of deep hydrous phase (DHP) including δ-AlOOH [3][4][5], phase H [6], HH-phase [7], and pyrite-type FeO 2 Hx [8,9], which were synthesized at conditions of cold mantle geotherm from natural minerals like diaspore (α-AlOOH) and goethite (α-FeOOH), provide possible mechanisms to transport a significant amount of water to the bottom of the mantle. The potential presence of hydrogen is likely to contribute a variety of seismological features observed at Earth's lower mantle.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of other elements (e.g., Al, Si, Mg) may also affect melting of P phase. A recent experimental study found that (Fe,Al)O 2 H (the solid solution phase of AlO 2 H and FeO 2 H) is stable at 107–136 GPa and 2,400 K (Zhang et al, ). Duan et al (), on the other hand, reported that AlOOH dehydrates at 2,500 K and 142 GPa.…”
Section: Resultsmentioning
confidence: 99%